Penyelenggaraan Dana Desa Berdasarkan Prinsip Akuntablitas Dan Transparansi Menurut Undang-Undang Nomor 6 Tahun 2014 Tentang Desa di Kabupaten Langkat - Hartina Hartina; Faisal Akbar; Mirza Nasution; Rosnidar Sembiring (Universitas Sumatera Utara, 2019)
Abstract. The implementation of the autonomy of the village led to the needs of a large Fund for each village to manage the Government's village. The construction of the rural area is a mix of development between villages in one district/city in an effort to speed up and improve the quality of service, development and empowerment of village community in the rural area through approach participatory development. Based on background. such research will be analyzed inaugural village Fund, channelling procedure mechanism budget funds from the state budget to the village village and barriers in the system of organizing the village Fund with the object of research done in the County Langkat. The implementation of village funds consists of original village income, Regional Budget and Expenditures (APBD) and State Budget (APBN). The administration of village government affairs which become village authority is funded from the Village Budget (APBDesa), central government assistance, and regional government assistance. Obstacles in the Village Fund Delivery System include the Low Synchronization Between Village and District Level Planning, the amount of Village Fund Allocation (ADD) as a support for government administration operations is still limited, Lack of intensity of Village Fund Allocation (ADD) socialization to the community, Village Government claims difficulties to prepare an Accountability that is in accordance with the specified standards. Keywords: village development, village fund, local government, state finance